Agronomic evaluation of rice (Oryza sativa) landraces for sustainable crop resilience in a changing climate - DE, ANIRNEETA; DEY, AVISHEK; RAHA, SUBRATA; KAR, DIPAK K (The Indian Journal of Agricultural Sciences, 2023)
Water scarcity and the adverse effects of climate change have significant impact on rice cultivation, leading to declining yields worldwide. The study focuses on red lateritic zone of West Bengal, where irregular rainfall and low water retention pose formidable challenges for farmers. The study was carried out at Zonal Drought Resistance Paddy Research Station, Hathwara, Purulia, West Bengal during 2021 and 2022 to evaluate the agronomic performance of selected landraces, known for their tolerance to stress. Characters like plant height, days to maturity, total grain/ plant, filled grains/plant, and spikelet fertility showed positive correlations with seed yield. Proline content and chlorophyll levels were higher in landraces as compared to the existing varieties. Findings suggest that late-maturing varieties exhibit tolerance mechanism while early varieties demonstrate an escape mechanism in response to water stress. The research underscores that by harnessing the genetic diversity of landraces rice breeding can be enriched to enhance resilience against changing climatic conditions. Overall, this study provides valuable insights into mitigating the impact of climate change on rice cultivation by utilizing landraces in breeding programs, ensuring food security, and supporting the livelihoods of vulnerable farming communities.